¿Has Utopia died? ¿Do Dystopias Triumph? - Tamayo, Juan José (2018)
The author analyzes the dialectical game between two philosophical conceptions in front of the problematic reality that we live: a utopian vision and the otherdystopian one. The first optimist, focused on the hope of a better world; and the second, pessimistic, deterministic, where there is no room for hope. The author analyzes, in the first place, the utopian reason, which sees the future with hope, in front of the scientific-technical reason, which is limited to living thepresent, starting from the analysis of Qohelet 3,1-8, which reflects a pessimistic philosophy. Secondly, it reflects on how difficult it is to live in utopia, in hope, it is like a dream impossible to achieve; with a clear predominance of dystopian vision. And, thirdly, it analyzes the need for a critical recovery of utopia, combining reason and hope; ending with a call to join all those who share this utopian vision.